CHALLENGES AND PROSPECTS FOR PUBLIC BUDGET MANAGEMENT IN UKRAINE - Павленко, Олена; Розмарина, Альбіна (SWorldJournal, 2025)
The article examines the current challenges and prospects for the development of public budget management in Ukraine. The authors analyze modern approaches to budget management to identify ways to improve the efficiency of the budgetary process. Cu